Case studies of problems associated with the employment of foreign workers in civil engineering projects - Mohd Yusop, Imran; Tan , Chin Keng (IIUM Press, 2011)
The inflow of foreign worker into Malaysia has been observed as causing many problems. The objective of this study is to determine the social and work related problems associated with the employment of foreign workers in civil engineering projects. Semi-structured interviews with four civil engineering contractors were conducted to explore the social-related and work-related problems associated with employment of foreign workers in civil engineering projects. The study concludes that the most critical social-related problems associated with the employment of foreign workers are disturbance of standard and quality of life, and jeopardising of the country’s ethnic balance whereas the work-related problems are on wage structure, excess number of workers, delay in work progress and disappearance of workers.